2018
DOI: 10.18203/2349-2902.isj20181420
|View full text |Cite
|
Sign up to set email alerts
|

Approach to hernial defect in laparoscopic incisional hernia repair

Abstract: Background: Ventral hernias are the second most common type of abdominal hernias and account for approximately 10% of all hernias. Recurrence rates after open suture repair have been reported to be as high as 31% to 49%. Laparoscopic ventral hernia repair (LVHR) has been reported to have reduced recurrence rates as compared to open mesh repair, reduced infection rate, shorter recovery time and hospital stay. During LVHR, closure of the hernial defect is a contentious issue. Author describe our observations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[ 62 ] and Nijas et al . [ 63 ] also concluded that the time for laparoscopic repair decreased with the progress in the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…[ 62 ] and Nijas et al . [ 63 ] also concluded that the time for laparoscopic repair decreased with the progress in the learning curve.…”
Section: Discussionmentioning
confidence: 99%